THE ENVIRONMENTAL MANAGEMENT SYSTEM OF THE SOUTH AFRICAN NATIONAL DEFENCE FORCE AT THE GRAHAMSTOWN MILITARY INSTALLATION - Magagula, Bheki (Scientia Militaria - South African Journal of Military Studies, 2014)
This article presents preliminary findings on current environmental management practices used by the South African National Defence Force (SANDF) at the Grahamstown Military Installation (GMI). These findings comprise interviews with SANDF officials and an analysis of official documents, which include the first and second editions of the Environmental Management Plan for Defence (2001 & 2008 respectively). The study on which this article reports, found that the emphasis placed on environmental protection within defence force activities worldwide has compelled the South African Department of Defence and Military Veterans (SA DODMV) to regulate the management of the environment within its properties. Yet, these efforts have faced numerous challenges that range from financial to human resources deficiencies. Consequently, the military installation at Grahamstown does not have environmentally knowledgeable and qualified personnel to deal with environmental issues. From the analysis of official documents as well as interviews with respondents, it was established that the SA DODMV itself does not have a budget for environmental services. The combination of all these drawbacks has led to the failure of the implementation of the Environmental Management System (EMS) for Defence at this military installation (i.e. GMI) of the SANDF. Undoubtedly, all these challenges have severely compromised the commitment of the SA DODMV to honour its environmental management obligations. Moreover, the deficiencies of all these resources undermine the sustainable utilisation of these national assets (natural resources) entrusted to the defence force. The study reported here proposes an ideal model for the successful implementation of the EMS in SANDF military installations.